Experimental comparison of closed cooling systems of photovoltaic modules - Alexander S. Sorogin; Rustam N. Khamitov; Sergey N. Zherebtsov (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The need to increase the efficiency of solar modules to 15–20% by cooling their surface, which in spring and summer is able to heat up to 70 ℃. Heat collection from photovoltaic modules is an additional opportunity to accumulate heat and use it for their own needs, especially for isolated power systems. The article discusses methods of closed cooling using tubes made of copper, metal plastic and stainless steel. All measurements were carried out in summer at a real, operating solar power plant located in the Crimea village of Karyernoe. Aim. To experimentally determine and identify the effect of the most efficient cooling system for photovoltaic modules. Methods. Methods of empirical research. In the experiment, sensors connected to the Arduino UNO system were used to measure the temperature and humidity of the ambient air, the temperature of the refrigerant at the inlet and outlet, and the data were recorded in an Excel table. Soudal FIX ALL adhesive sealant is used to fix the cooling system. Results and conclusions. The authors have obtained volt-ampere characteristics, refrigerant inlet and outlet temperatures, photovoltaic modules surface temperatures. The cooling system made of stainless steel pipes showed the greatest cooling efficiency of the solar module, which allowed reducing the module temperature from 66 to 38℃ at some points. This increased the efficiency of photoelectric module by 3.5% relative to the rated power. The heated liquid from the photoelectric module has cooled down to its original temperature values, thanks to the installed cooling radiator, for the possibility of reuse of the liquid in the solar panel cooling circuit.